Letter (copy) : Transport of war materials to Spanish rebels - Citrine, Walter, 1887-1983
023_0027_001 International. 30th November 1936. Mr. Edo Fimmen, International Transport Workers' Federation, Vondelstraat, 61, Dear Edo, TRANSPORT OF WAR MATERIALS TO SPANISH REBELS. I have your letter of the 27th instant, and thank you very much for the very useful information contained therein. I am just wondering whether it would be possible for you to ascertain the dates when the steamers referred to left their loading ports, and the dates of their arrival in Spain. Yours sincerely, General Secretary. 292/946/23/30